Antihypertensive Peptides from Milk Proteins - Heikki Vapaatalo; Pauliina Jäkälä (MDPI AG, 2010)
Dietary proteins possess a wide range of nutritional and functional properties. They are used as a source of energy and amino acids, which are needed for growth and development. Many dietary proteins, especially milk proteins, contain physiologically active peptides encrypted in the protein sequence. These peptides may be released during gastrointestinal digestion or food processing and once liberated, cause different physiological functions. Milk-derived bioactive peptides are shown to have antihypertensive, antimicrobial, immunomodulatory, antioxidative and mineral-binding properties. During the fermentation of milk with certain lactobacilli, two interesting tripeptides Ile-Pro-Pro and Val-Pro-Pro are released from casein to the final product. These lactotripeptides have attenuated the development of hypertension in several animal models and lowered blood pressure in clinical studies. They inhibit ACE in vitro at micromolar concentrations, protect endothelial function in vitro and reduce arterial stiffness in humans. Thus, milk as a traditional food product can after certain processing serve as a functional food and carry specific health-promoting effects, providing an option to control blood pressure.